Relação entre o controle postural e as habilidades orais em crianças pré-termo - Ruedell, Aneline Maria (2009)
This study aimed to verify the relationship of postural control and oral skills. The mixed longitudinal study, consisted of 43 children ages 4, 6 and 9 months of corrected age, a total of 80 ratings. The positions of prone, supine, sitting and standing, were evaluated according to the Alberta Infant Motor Scale (AIMS). The sitting and prone were classified as appropriate and not appropriate for the ages assessed in accordance with the senior representative of each position of the AIMS, which demonstrated the month in which 90% of children had each position. The development of oral skills was through the movement of lips, tongue and jaw during bottle-feeding / breast withdrawal pasty the spoon, the use of the cup and biscuits. The planes of movement, sagittal, frontal and transverse behavior were analyzed in the postural and oral skills. All evaluations were videotaped and analyzed by 3 physiotherapists and speech therapists 3. The parents answered a questionnaire with closed questions on eating behavior and attitudes usual, the child during the day. Later, there was a statistical analysis to test interrater reliability, Fisher's test to verify the relationship between postural control and oral skills and Kruskal-Wallis test for comparison between ages. The motor development was late, especially at 4 and 6 months and an evolution from the sixth month. In analyzing the survey, found that no family had the habit of placing the child in a prone position. Most parents are not encouraged to sit at 6 months, while at 9 months, most children were encouraged in this position. In relation to oral skills, some of them were not complete in all children, like, lip seal, lip pressure, lateralization of language and rotation of tongue and jaw. However, there was a progressive development of these movements over the months. In analyzing the data of postural control and oral skills has not been verified relationship between them, because the movements of the oral structures were more developed than postural control.